Analisis Pelatihan Kewirausahaan dalam Meningkatkan Kemampuan Berwirausaha Pada Kelompok Usaha Pemberdayaan Perempuan di Desa Mundusewu Kecamatan Bareng Kabupaten Jombang - Charisma Nur Aini; Bambang Septiawan; M. Adib Mawardi; Redy Khoirianto (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is to determine the extent of the implementation of training in women's empowerment groups in Mundusewu Village Bareng District Jombang Regency, how the entrepreneurial activities of women's empowerment groups in Mundusewu Village Bareng District Jombang Regency in training groups and supporting factors women empowerment efforts in Mundusewu Village, Bareng District, Jombang Regency. The data collection technique used in this study was to conduct in-person interviews with informants and documentation studies. The method of data analysis used was descriptive analysis. The results of the study show that the implementation of training provided by the Jombang Regency Labor Department in the form of entrepreneurship training Social Media and Broadcaster in improving entrepreneurial abilities is very influential, then the entrepreneurial activities of women's empowerment groups in Balamatan Munduse Village. well, when the training provided by the Jombang Regency Labor Department. Inhibiting factors in this case. The first is, there is within the building members themselves, namely regarding the mindset of someone who wants to progress and grow by following women’s empowerment training. While the supporting factor, namely the cooperation and enthusiasm of KSM Probo Ndeso building members who always participate in the training, and take an active role in the creation of content efforts to increase the sales of existing SMEs. Secondly, there is support from the government down as well as being part of the sustainability of the content channel as well as providing facilities to support content creation.